Market Reaction to the Announcement of Stock Split (Study on Companies Listed on the Indonesia Sharia Stock Index) - Vindy Fortuna; Edyanus H Halim; Fauzan Fathoni (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
Stock split is one of the corporate actions that a company can take. Corporate action is an action taken by a company that has a direct impact on share ownership of shareholders. This study aims to examine the market reaction to the announcement of stock split and see if there is a difference in abnormal returns before and after the announcement of the stock split. The population in this study are companies that are listed in the Indonesian Sharia Stock Index and conducted a stock split in 2019. This study used 8 companies that met the criteria as samples. This study used the analysis method of paired-sample t-test and Wilcoxon signed ranks test, using SPSS software to process data. The results of this study indicate that there is no difference in abnormal returns before and after stock split in the Indonesian Sharia Stock Index in 2019. This shows that there is no information contained on the stock split announcement or there is information content on the stock split but the market does not react to the announcement.